A study on pollution emission flux estimation and tailwater for mariculture in the Tianjin, China - Yuan Hui; Liu Jiahong; Tian Ye; Han Shaoqiang; Zhai Haojie (E3S Web of Conferences)
With the rapid development of marine aquaculture in Tianjin, the methods and types of aquaculture are constantly evolving and changing. Due to the presence of large amounts of pollutants such as nitrogen and phosphorus in aquaculture wastewater, it has gradually become a concern for marine environmental issues in the near sea. To understand the characteristics of pollution emissions from marine aquaculture in Tianjin, we evaluated the production data of marine aquaculture from 2014 to 2023 using the Pollution Coefficient Method (PCM). The results showed that the average pollution emission fluxes of total nitrogen (TN), total phosphorus (TP), ammonia nitrogen (NH3-N), and chemical oxygen demand (COD) were 117.3 t a-1, 8.0 t a- 1, 8.2 t a-1 and 37.5 t a-1, respectively. COD and TN are the main pollutants generated during the seawater aquaculture process in Tianjin. Meanwhile, the research results indicate that with the implementation of the Bohai Comprehensive Management Action Plan (CMAP-BS) and seawater aquaculture standards, effective reduction of pollutant emissions has been achieved, while also promoting the sustainable development of seawater aquaculture.